DEVELOPMENT OF LEARNING MODULES BASED ON PROJECT BASED-LEARNING TO IMPROVED STUDENT’S ABILITIES TO SPEAK ENGLISH - SILVIA EKASARI (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2020)
This research is to design an English based learning module for project-based learning. Teaching material and training assignments are provided, designed for English subjects so that they are easy for students to understand and the context is adapted to students' daily lives. This approach is expected to enable students to improve their cognitive and psychomotor levels in English language learning and focus on how to observe and understand the modules presented. The development model uses the ADDIE model. The development procedures carried out following the ADDIE design, the steps are: 1. Analysis; 2. Design (design); 3. Development (development); 4. Implementation (implementation); 5. Evaluation (evaluation). Module development by showing the existing criteria and procedures is quite effective. Teachers and students at the time of the field test gave a positive assessment of the learning modules that were developed. Based on the test results it can be concluded that both the results of expert validation and field trials that the quality of the Project Based-Learning English Based Learning Module is good and very effective for increasing the cognitive and psychomotor levels of students